Utilizing wWiMAX Mesh model for efficient IPTV transmission - Uluğ, Seçkin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this thesis, an alternative model is proposed for the distribution of IPTV in wireless environment. Considering the data rate requirements of the IPTV service and challenges in distribution of the service due to wireless environment, our proposed model is built on the Mesh operating mode of the standard IEEE 802.16 (a.k.a, WiMAX). Besides the high data rates provided by the WiMAX technology, the capability of relaying transmissions and the adaptability to changing environment brings the WiMAX Mesh mode as a viable alternative to the infrastructure based models. In our proposed model, the standard WiMAX Mesh mode is modi ed in order to meet the strict delay requirements of the IPTV service. Accordingly, transmissions are carried over only high data rate links and connections with up to two hops to the BS are allowed. Additionally, bene ting from space diversity information, parallel transmissions are utilized to save transmission slots, and allow serving more users. The simulation results show that, for the given delay constraints, the proposed model improves capacity compared to the standard WiMAX Mesh mode at the cost of omitting a few nodes (less than 1%) for which the experienced channel quality is too low for IPTV service anyways.
Keywords: Broadband communication systems.; IEEE 802.16 (Standard); Mobile communication systems.; Wireless LANs -- Standards.; Wireless communication systems.